What we don't know may hurt us: Urinary drainage system tubing coils and CA-UTIs-dA prospective quality study - (:unkn) unknown (MOSBY-ELSEVIER, 2013)
Catheter-associated urinary tract infections account for >30% of infections in acute care hospitals. We hypothesized that coiling of/kinks in the indwelling urinary bladder catheter (IUBC) drainage bag tubing would increase the occurrence of infection/bacteriuria. Ninety-one patient events were evaluated over 60 days. All outcome variables trended with greater frequency among those with a coil in the IUBC tubing; only fever (temperature > 38.1 degrees C) correlated significantly between groups (P = .003). If IUBC is unavoidable, strategies such as keeping collection bag below the level of bladder and avoiding any coiling in the drainage system should be employed. Further study of these phenomena is needed. Copyright (C) 2013 by the Association for Professionals in Infection Control and Epidemiology, Inc. Published by Elsevier Inc. All rights reserved.
Keywords: Indwelling urinary bladder catheter; Catheter-associated urinary tract infection; Infection; Coiled tubing; Fever; TRACT-INFECTION; PREVENTION